Herramientas y modelos tecnológicos para la gestión del conocimiento en el desarrollo de software: Una revisión sistemática y análisis de impactos y desafíos - Campos Salcedo, Julio (2025)
This study provides a systematic review of knowledge management in software development over the last decade (2015-2025), using scientific databases such as Scopus and WoS. Key industry tools were analyzed, including Jira, Confluence, Draw.io, and Teams, which facilitate collaboration, documentation, and process visualization. The effectiveness of the SECI model was highlighted as a theoretical framework for transforming tacit knowledge into explicit knowledge, especially in agile environments. The results identified recurring challenges, such as interoperability, lack of standardization, and resistance to change, which hinder the adoption of technological solutions. However, the analyzed tools demonstrated their ability to improve collaboration, facilitate access to information, and foster efficiency and innovation. This study suggests that integrating established tools with robust theoretical frameworks like the SECI model could be an effective solution for knowledge management in software development. Future studies could focus on developing technological models that combine these tools with adaptive approaches, facilitating their adoption and improving outcomes in organizations.